Conjugating Existing Clinical Drugs With Gold Nanoparticles for Better Treatment of Heart Diseases - Jingwen Zhang; Aiqun Ma; Lijun Shang (Frontiers in Physiology, 2018)
Developing new methods to treat heart diseases is always a focus for basic research and clinical applications. Existing drugs have strong side-effects and also require lifetime administration for patients. Recent attempts of using nanoparticles (NPs) in treating atherosclerosis in animals and some heart diseases such as heart failure and endocarditis have provided hopes for better drug delivery and reducing of drug side-effects. In this mini-review, we summarize the present applications of using gold nanoparticles (GNPs) as a new drug delivery system in diseased hearts and of the assessment of toxicity in using GNPs. We suggest that conjugating existing clinical drugs with GNPs is a favorable choice to provide “new and double-enhanced” potentiality to those existing drugs in treating heart diseases. Other applications of using NPs in the treatment of heart diseases including using drugs in nano-form and coating drugs with a surface of relevant NP are also discussed.